2013
DOI: 10.1007/s12022-013-9248-9
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated (Anaplastic) Thyroid Carcinoma and Iodine Intake in Salta, Argentina

Abstract: This study was conducted to investigate the natural history of undifferentiated thyroid carcinoma (UTC) in the iodine-deficient province of Salta, Argentina, in relation to salt iodization and health care standards. Five hundred ninety-three thyroid cancers diagnosed from 1958 to2012 were reviewed based mainly on the WHO classification and grouped into three periods, one before and two after iodine prophylaxis. The incidence of UTC was analyzed in relation to changing concentrations of potassium iodide (KI) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Northern Argentina in 1960 was severely iodine deficient and mean UI excretion was 20 μg/day [ 103 ]. After iodized salt was introduced, mean UIC increased into the sufficient range, and was 152 μg iodine/g creatinine in 1975.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Northern Argentina in 1960 was severely iodine deficient and mean UI excretion was 20 μg/day [ 103 ]. After iodized salt was introduced, mean UIC increased into the sufficient range, and was 152 μg iodine/g creatinine in 1975.…”
Section: Reviewmentioning
confidence: 99%
“…After iodized salt was introduced, mean UIC increased into the sufficient range, and was 152 μg iodine/g creatinine in 1975. Over this period, the percentage of thyroid cancer that was ATC decreased from 15.2 % before salt iodization to 2.6 % after salt iodination, and the annual incidence decreased from 1.4 per million to 0.1 per million [ 103 ]. A plausible explanation for why the percentage of thyroid cancer that is ATC is higher in areas of severe iodine deficiency is that when goiter is endemic in a population, individuals are less concerned by the occurrence of thyroid nodules or swelling, and this may delay diagnosis in many cases until serious symptoms occur.…”
Section: Reviewmentioning
confidence: 99%
“…Passaro et al (5) reported that ionizing radiation enhances the cell death of oncolytic adenovirus dl922-947 in ATC. Increased iodine intake contributes to a lower incidence of ATC (6), and it has been reported that forkhead box o3a enhances the proliferation of ATC cells via regulating the transcription factor, cyclin A1 (7). In addition, several pathways involved in the progression of ATC have been identified, including the Notch1 signaling pathway, phosphoinositide 3-kinase/Akt signaling pathway and the epidermal growth factor receptor/extracellular signal-regulated kinase pathway (810).…”
Section: Introductionmentioning
confidence: 99%
“…9 A similar observation about the incidence of ATC after higher salt iodination was reported in other endemic goiter regions, namely the Tyrol region in Austria and Argentina. 18,19 In contrast to differentiated thyroid cancer, which often has a subtle clinical presentation and may be difficult to detect, ATC is correctly diagnosed in nearly all cases in countries with adequate health care because of rapid tumor growth and the clinical presentation. 9,20 Risk factors for ATC are: a history of goiter or a prior co-existing differentiated thyroid cancer [21][22][23] , insufficient iodine in the diet 9, 18,24,25 , low level of education 21 , type B blood group 21 , and presence of TERT mutation in coexisting thyroid papillary carcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%